Chitosan–Nanocellulose Edible Coating Enriched with Essential Oils to Reduce Shrinkage and Extend the Shelf Life of Fresh Red Chilies - manurung, Matias Julfan (Cattleya Darmaya Fortuna, 2025)
The shelf life of fresh red chili is limited by transpiration, respiration, tissue softening, and microbial growth. This study evaluated chitosan–nanocellulose (Chi–NC)-based edible coating enriched with lemongrass essential oil (MA) to suppress losses and extend shelf life in cold storage. A completely randomized design with 4 treatments was used: Control (without coating), Chi–NC, Chi–NC+MA 0.2%, Chi–NC+MA 0.5% (n=3; 10 ± 1 °C; RH 85–90%; 12 days). Parameters: weight loss (WL, %), firmness (N), color (ΔE, a*), TPC (log CFU/g), unmarketable fruit (%), and shelf life estimation (TPC limit 6 log CFU/g and/or ΔE>5). The results showed that 0.5% Chi–NC+MA reduced WL day-10 from 12.0% (control) to 6.1%, maintained firmness (18% vs. 35% reduction), decreased TPC (4.9 vs. 6.2 log CFU/g), and delayed the 6-log TPC limit by 4 days. The estimated shelf life increased to ±11 days at 10 °C. The Chi–NC+MA formulation is feasible to be adopted to reduce post-harvest losses of chili.